The development of Vi-Connect: An educational game for the social inclusion at school of students with vision impairment. - Ifigeneia Manitsa; Maria Livanou; Stephanie Burnett Heyes; Fiona Barlow-Brown; Nuria Gardia; Olivia Siegfried; Zoe Clarke; Holly Coelho; Alberto De Caro (PLoS ONE)
Students with vision impairment experience multiple social emotional challenges at school which stem from communication difficulties in the social relationships they develop with teachers and classmates. This study took a multi-method, multi-informant participatory approach to develop "Vi-Connect: A Social School Journey", a digital intervention in the form of an educational game aimed at promoting school social inclusion of students with vision impairment by scaffolding advocacy and social communication skills. The study consisted of three phases: Co-production before developing Vi-Connect (Phase 1), development of the prototype (Phase 2) and assessment of Vi-Connect (Phase 3). Four and five adolescents with vision impairment participated in Phases 1 and 3 of the study respectively. A second group of young people from Eye-YPAG (N = 8), a youth advisory group for eye and vision research, participated in Phase 1. Six professionals in the field of vision impairment participated in Phases 1 and 3. Reflexive Thematic Analysis was used to analyse the findings of Phases 1 and 3. A prototype of Vi-Connect including three school-based scenarios was developed based on the Curriculum Framework for Children and Young People with Vision Impairment and the experiences and suggestions of all participants. The findings of this study indicated that digital interventions can be an additional supportive educational tool to support the social inclusion of students with vision impairment, as they can facilitate coping with challenging social situations and promote self-advocacy. This is one of the first studies to involve students with vision impairment in intervention development, prioritising the lived experiences of this student population. Additionally, acknowledging the key role of professionals in the school inclusion of students with Special Educational Needs and Disabilities, this study involved professionals in the field of vision impairment. This research opens the field for the development of more accessible educational interventions for students with sensory impairments.